Standardisation of MEDIUM FOR MICROPROPAGATION OF RECALCITRANT POTATO (Solanum tuberosum L.) cultivar Kufri Jyoti - Venkatasalam, E P; Latawa, Jyoti; Chakrabarti, S K; Pandey, K K; Sood, Richa; Thakur, Vandana; Sharma, Ashwani K; Singh, B P (Potato Journal, 2016)
Experiments were conducted to devise an efficient micro-propagation medium for mass multiplication of a high yielding but recalcitrant potato cultivar Kufri Jyoti using nodal explants with different concentrations and combinations of NH4NO3, GA3 and NAA. Virus-indexed nodal cuttings established in full-strength Murashige and Skoog (MS) basal salts and vitamins, supplemented with 0.29 Î¼M GA3 and 0.05 Î¼M NAA was used as explants for the experiment. Among the various media tested, MS medium with increased level of ammonium nitrate (25.79 mM) supplemented with GA3 (0.58 Î¼M) and NAA (0.1 Î¼M) was found to be optimum as it significantly improved the shoot length, number of leaves, number of nodes and inter nodal length after 21 days of sub-culturing. The next higher concentration of ammonium nitrate (30.94 mM) supplemented with GA3 (0.58 Î¼M) and NAA (0.1 Î¼M) also exhibited statistically at par response in most of the morphological characters but higher concentration (41.25 mM) retarded all the parameters studied.